2020
DOI: 10.21203/rs.3.rs-42008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time in Therapeutic Range, Quality of Life and Treatment Satisfaction of Patients on Long-Term Warfarin for Non-Valvular Atrial Fibrillation: A Cross-Sectional Study

Abstract: Background:The use of warfarin in patients with non-valvular atrial fibrillation (NVAF) can be challenging. In this study, we evaluate the time in therapeutic range (TTR), health-related quality of life (HRQoL) and treatment satisfaction of patients on long-term warfarin for NVAF. The HRQoL and treatment satisfaction were compared based on the TTR.Methods:A cross-sectional study was conducted among patients on warfarin for NVAF who attended the anticoagulant clinic of a tertiary cardiology referral center in S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…OACs are prescribed for patients with AF to decrease their risk of stroke [45]. While OACs do not directly affect patients' symptoms, it may provide relief for patients knowing they are at a much lower risk of developing stroke and therefore may improve their AFQoL [45,46]. Interestingly, we found that use of OACs was signi cantly associated with a higher odds of poor AFQoL.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…OACs are prescribed for patients with AF to decrease their risk of stroke [45]. While OACs do not directly affect patients' symptoms, it may provide relief for patients knowing they are at a much lower risk of developing stroke and therefore may improve their AFQoL [45,46]. Interestingly, we found that use of OACs was signi cantly associated with a higher odds of poor AFQoL.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding COPD, a plausible reason for poorer AFQoL is that patients who experience frequent exacerbations of their COPD symptoms may be at an increased risk of experiencing frequent episodes of AF symptoms and potential rapid ventricular response [44]. OACs are prescribed for patients with AF to decrease their risk of stroke [45]. While OACs do not directly affect patients' symptoms, it may provide relief for patients knowing they are at a much lower risk of developing stroke and therefore may improve their AFQoL [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of low-dose NOAC prescription and lower TTR for warfarin treatment were found in the present cohort. Notably, these patterns of prescription seem to be common in clinical practice [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…15 This attrition may reflect difficulty in managing and sustaining warfarin self-management, and raises the potential of study bias. Another study reported that health-related quality of life was independent of TTR, 16 highlighting the need for quality of life to be included as a separate outcome in warfarin self-care studies. One costeffectiveness study modeled VKA therapy self-testing/selfmanagement compared with usual care over 10 years.…”
mentioning
confidence: 99%